Psychological Autopsy: A Powerful Tool in Forensic Investigations - Sara Sablone; Mara Bellino; Andrea Nicola Cardinale; Maria Grazia Violante; Roberta Risola; Antonella Magno; Vincenzo Pierro; Ignazio Grattagliano (Forensic Sciences)
Background: A psychological autopsy is a post-mortem investigative tool used to carry out a retrospective reconstruction of a missing subject’s life. The method includes gathering information from all the potentially involved parties, which may indicate the relevant elements directly or indirectly to trace the victim’s experience and identify personality traits, lifestyle, and interpersonal relationships. Discussion: Psychological autopsies are mainly performed during criminal investigations to identify the cause of death and the specific circumstances (natural, accidental, suicidal, or homicidal death). In addition, from an epidemiological point of view, this method aims to collect the relevant information about an individual’s behavior, circumstances, and reasons for their death to identify common risk factors to prevent new suicides. Although less frequently, this tool can also serve other purposes, such as the legal validity estimation of pre-death actions. Moreover, it may be used to assess whether mistakes have been made in treating people undergoing medical or psychological treatment. Conclusions: Currently, this methodology still has a limited diffusion on the Italian and European scenes due to the lack of standardized guidelines and substantial relevant scientific literature. It is the main factor affecting the tool’s reliability, validity, and systematic application in forensic investigations.